Christelike universiteit en politiek in 'n apartheids- en post-apartheidsbedeling - Botha, M. Elaine (Koers, 1995)
Christian university and politics in an apartheid and post apartheid society. An university is always integrally related to its surrounding culture. The critical question in this regard is the extent to which it takes its cues for the fulfilment of its task from the political establishment within which it is situated and has to function. This issue has historically been of central significance to the Potchefstroom University for Christian Higher Education and still represents a challenge within the new political dispensation. It is argued that the PU for CHE's understanding of the nature of a Christian university and Christian scholarship was influenced, even determined by its uncritical political position within the apartheid society, that this state of affairs was not addressed by the apolitical stance advocated by the university authorities and even less by the Christian philosophy of H.G. Stoker. This stance towards the political dispensation needs radical rethinking in the light of challenges posed by die post-apartheid political dispensation.